Predictions and pandemics: why economies relapse before they recover - Roach, Stephen (Henry Stewart Talks, 2021)
Recession, Economic recovery, Double-dip recession, Economic prediction, Statistical analysis, Economic aftershock, Covid-19 – Economic policy, Business structure, Employment